Presenting a Framework for Evaluating and Prioritizing Risk of Information Technology Outsourcing: Perspective of Experts in Information Systems Design - abbas Keramati (Journal of Information Technology Management, 2012)
Information technology outsourcing projects have advantages including: reduced costs, improved service quality, creation of competitive advantage, etc. When these projects are being outsourced, lack of attention to their risks causes the lost of anticipated benefits and contributes to failure. As for the growing trend of information technology outsourcing projects in Iran, the purpose of this study is to identify the risks of information technology outsourcing projects, evaluate and prioritize them based on the perspective of experts in information systems design. For achieving these goals, key articles were reviewed and comprehensive list of 12 risk factors were identified. For prioritizing, a Fuzzy Analytical Network Process (F-ANP) structure has been provided and the risk factors were laid in it. Then, by using a questionnaire, 13 experts' viewpoints were collected. The results show that the factor of "supplier" and the sub-factor of "Lack of skills of supplier in IT operations" are the most important factors for success and failure of information technology outsourcing projects in the perspective of experts in information systems design.